2017
DOI: 10.1186/s40164-017-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate use of ruxolitinib in acute and chronic graft versus host disease refractory both to corticosteroids and extracorporeal photopheresis

Abstract: BackgroundRuxolitinib is a potent inhibitor of JAK1/2 with proven efficacy in myelofibrosis. In recent years, research in graft versus host disease (GVHD) has revealed the role of activation of JAK pathways in alloreactive lymphocytes. Some reports have shown significant responses in refractory GVHD patients.Cases presentationIn this report we present our experience in 8 patients with acute or chronic GVHD with refractoriness to steroids and extracorporeal photopheresis treated with ruxolitinib. Three patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In vitro, T cells exposed to ruxolitinib had reduced proliferation and cytokine production in response to alloantigen , and in vivo treatment with ruxolitinib reduced GVHD severity in treatment‐naive and steroid‐refractory major histocompatibility complex–mismatched murine models . In published case series and retrospective reviews, complete response (CR) rates of 8%–46% and overall response rates (ORR) of 38%–82% were reported for adult and pediatric patients with aGVHD refractory to steroids alone or in addition to other immunosuppressive drugs . Herein we provide a summary of the Food and Drug Administration's (FDA's) review of ruxolitinib for treatment of SR‐aGVHD based on the first prospective trial, the REACH‐1 Study.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, T cells exposed to ruxolitinib had reduced proliferation and cytokine production in response to alloantigen , and in vivo treatment with ruxolitinib reduced GVHD severity in treatment‐naive and steroid‐refractory major histocompatibility complex–mismatched murine models . In published case series and retrospective reviews, complete response (CR) rates of 8%–46% and overall response rates (ORR) of 38%–82% were reported for adult and pediatric patients with aGVHD refractory to steroids alone or in addition to other immunosuppressive drugs . Herein we provide a summary of the Food and Drug Administration's (FDA's) review of ruxolitinib for treatment of SR‐aGVHD based on the first prospective trial, the REACH‐1 Study.…”
Section: Introductionmentioning
confidence: 99%
“…Ibrutinib is a combined BTK/ITK inhibitor known to be efficacious in treatment of murine and human cGVHD, for which it is currently the only FDA-approved drug (42, 43). The Jak1/Jak2 inhibitor, ruxolitinib has been in case studies and is currently in Phase 2 and 3 clinical trials for use in steroid-refractory cGVHD (44–46). Mast cells express many of the signaling molecules targeted by these drugs, and we therefore investigated whether chemokine production would be inhibited when treated with ibrutinib or ruxolitinib (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Zeiser et al reported in their landmark paper data from 95 patients with steroid-refractory acute (n=54) and chronic (n=41) GvHD and described for both groups a response rate above 80% [5]. Other investigators published data from 8 to 13 patients: Maldonado et al described in eight younger patients with acute and chronic GvHD a response rate of 100% (CR n=3, PR n=5) and Assouan et al were successful with a partial or complete remission in 7/10 patients [9, 10]. Another group described use of ruxolitinib for GvHD treatment in paediatric patients suffering from acute GvHD [11].…”
Section: Discussionmentioning
confidence: 99%